Investigating Studentsâ€™ Academic Stress on the Transition to Online Learning During the Covid-19 Pandemic - Rosdialena Rosdialena; Zulvia Trinova; Erna Dewita; Nurhamsi Deswila; Fadil Maiseptian (AT-TA'LIM, 2021)
This research is based on the situation of students at the State Islamic University Imam Bonjol Padang that were stressed due to the changing Â of learning process into online learning during the pandemic of covid-19.The study aims to describe students state based on physical response, emotion, and behaviour. Quantitative method with descriptive approach were used. The objects of the research were chosen based on Random sampling. The instrument used in the research were questionnaire based on Likert. The research found that the level of academic stress based on physical response was high at 68 %, while in emotional response was 70 % and 65 % based on behaviour. The result of the research can be used as data to improve the quality and innovation of teaching and learning during the pandemic to avoid greater issues.